European intellectual history from Rousseau to Nietzsche - Turner, Frank M. (Frank Miller), 1944-2010 (Yale University Press, 2014)
Turner's lectures "distilled modern European history from the Enlightenment to the dawn of twentieth century and conveyed the turbulence of a rapidly changing era in European history through its ideas and leading figures."--Jacket